2008
DOI: 10.1504/ijss.2008.016087
|View full text |Cite
|
Sign up to set email alerts
|

Enabling superior m-health project success: a tricountry validation

Abstract: The healthcare industry is facing increasing pressures to embrace new technologies that support greater patient access to, and higher quality of (but at the same time offer cost-effective), healthcare delivery. This pressure has spawned a plethora of initiatives to embrace the possibilities and potentials of technologies to develop and then diffuse new devices, new pharmaceutical products and support minimal invasive surgical techniques that will facilitate superior healthcare delivery. Pursuing such initiativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 9 publications
(10 reference statements)
0
14
0
Order By: Relevance
“…In fact, the solution is very similar to Short Message Service (SMS) applications which are renowned for their popularity (Mackay & Weidlich, 2007;O'Doherty et al, 2010;Oh et al, 2008). It is, therefore, anticipated that diabetes sufferers will find the solution easy to use and useful as also supported in preliminary studies and assessments in previous trials both in the US and Canada (Wickramasinghe & Goldberg, 2004Wickramasinghe, Goldberg, & Bali, 2007. Additionally, healthcare professionals that have used the proposed solution have indicated that the functionality that concerns them (Figure 3) is also easy to use and useful (Wickramasinghe & Goldberg, 2004Wickramasinghe, Goldberg, & Bali, 2007.…”
Section: Task Complexitymentioning
confidence: 94%
“…In fact, the solution is very similar to Short Message Service (SMS) applications which are renowned for their popularity (Mackay & Weidlich, 2007;O'Doherty et al, 2010;Oh et al, 2008). It is, therefore, anticipated that diabetes sufferers will find the solution easy to use and useful as also supported in preliminary studies and assessments in previous trials both in the US and Canada (Wickramasinghe & Goldberg, 2004Wickramasinghe, Goldberg, & Bali, 2007. Additionally, healthcare professionals that have used the proposed solution have indicated that the functionality that concerns them (Figure 3) is also easy to use and useful (Wickramasinghe & Goldberg, 2004Wickramasinghe, Goldberg, & Bali, 2007.…”
Section: Task Complexitymentioning
confidence: 94%
“…In many ways, this emerging area is being heralded as the best way for information technology (IT) to facilitate patient-centric healthcare delivery 2 , 3 . Moreover, it facilitates and enables empowerment and superior self-management 2 3 4 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, CHI promises a new era of health computing services that will not only help to serve patients but also providers and thus impact, in a positive way, the other healthcare web of players including healthcare organizations, payers, and regulators 3 . A large part of consumer health informatics is focused around prevention, self-management, and providing individual consumers with the technologies and information they need to better manage their health and wellness 1 2 3 4 5 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations